Measuring Social Capital in the Prison Setting: Lessons Learned From the Inmate Social Capital Questionnaire. (October 2018) - Lafferty, Lise; Chambers, Georgina M.; Guthrie, Jill; Butler, Tony; Treloar, Carla
Social capital has been associated with improved health outcomes. Measures of social capital have been developed specifically for different population groups, cultures, and contexts; however, there is no readily available measure for use among inmates in the prison setting. This study sought to translate a community concept into the prison setting through the development and piloting of the Inmate Social Capital Questionnaire (ISCQ). Thirty male inmates (living with hepatitis C) participated in the pilot phase of the ISCQ ( n = 23 sentenced and n = 7 held on remand). Dimensions of social capital were influenced by length of incarceration (time already served as well as time to release), connections with family, and duration at current prison.